Culture. Science. Education: Current Issues - Kuklina A. S., Kuklina I. G., Lesokhina A. M., Shchankina L. N., Gutova S. G., Kholopova A. K., Balan A. V., Pisareva E. V., Shevchenko E. I., Berezkina I. V., Malkanduev I. A., Khanbabaeva O. E., Kvashnin P. R., Makhkamova S. I., Rezak E. V., Sabodina E. P., Melnikov Y. S., Mikhalchenkova N. A., Bolshakov S. N., Bolshakova I. M., Kulikova N. V., Krasilnikova S. V., Arshinik S. P., Lysenko V. V., Kostenko E. G. (Culture. Science. Education: Current Issues, 2020)
researches of synthesis and polymerization of the reactive polymers have been conducted. Polymerization features of monoallyl, diallyl, quaternary ammonium surfactants, in particular, diallyl dialkylammonium halogenides and dimethylaminoethyl methacrylat are considered in the article. Certain results of researches in the field of synthesis and studying of properties of some polymers and copolymers with the halogen-containing heterocyclic compounds leading to formation of monomeric quaternary salt are studied in more detail as well as the attempt to generalize results of reactions of chemically active polymers is made.
Keywords: синтез; synthesis; полимеризация; четвертичные аммониевые соли; сополимеры; функциональные группы; гетероциклические соединения; polymerization; quaternary ammonium salts; copolymers; functional groups; heterocyclic compounds